YNiCoSx / NCF catalyst and preparation method thereof
By introducing Y and S on the NiCo foam matrix through a one-step hydrothermal method, the YNiCoSx/NCF catalyst was prepared, which solved the problem of low efficiency of electrolytic catalysts in the prior art, and achieved efficient and stable electrocatalytic performance of water cracking, surpassing that of the above-mentioned The performance of some precious metal catalysts is achieved.
Patent Information
- Application Number
- CN202411357361.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The prior art lacks efficient and low-cost electrolytic bifunctional catalysts, especially in the study of introducing rare earth elements as electrolytic catalysts, the impact of the incorporation of Y elements on non-precious metal-based compounds and their mechanism of action are unclear.
Y and S were introduced on the NiCo foam matrix by one-step hydrothermal method to prepare the YNiCo trimetal sulfide catalyst (YNiCoSx/NCF) with a multiphase structure in situ. By optimizing the reaction conditions and proportions, the conductivity and structure of the catalyst are improved. stability.
The HER and OER performance of the catalyst is significantly enhanced under alkaline conditions, which is far superior to commercial Pt/C and RuO2, and shows excellent electrocatalytic activity and stability, can operate for a long time at high current density and low voltage, Suitable for electrolytic water cracking applications.
Smart Images

Figure CN119307963A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a YNiCoS x / NCF catalyst and preparation method thereof. Background Art
[0002] Rational design and synthesis of efficient and low-cost bifunctional catalysts for water electrolysis remain a challenge. Transition metal sulfides (TMSs) with good electrical conductivity and tunable electronic structure are potential candidates to replace precious metal electrocatalysts. Among the recently developed metal chalcogenide-based oxygen evolution reaction (OER) catalysts, nickel (Ni) and cobalt (Co)-rich chalcogenides have received much attention due to their superior OER activity and stability. Jiang et al. prepared three crystalline nickel sulfides, NiS, NiS2, and Ni3S2, via a microwave-assisted route. Electrochemical studies showed that Ni3S2 had the highest HER activity among the three forms, which was attributed to its structural advantages, including unique surface chemistry, large electrochemically active area, and high electrical conductivity.
[0003] In addition, the performance and stability of the alloy can be improved by introducing foreign elements. In recent years, the catalytic properties of rare earth catalytic materials have been widely studied worldwide. Rare earth elements, covering lanthanide elements (atomic numbers 57 to 71) and scandium and yttrium with similar electronic structures and chemical properties, exhibit excellent multi-faceted properties due to their unfilled 4f electron orbitals. These properties allow rare earths to show unique chemical characteristics in the field of catalysis. Recent studies have emphasized that the special electronic structure of rare earths has a significant impact on the energy conversion and storage capacity in catalysis, especially in improving activity and stability. Rare earth elements have also promoted the development of new properties including the formation of intermetallic compounds, adsorption / desorption processes, reaction selectivity, surface interactions, and improved hydrogenation / oxidation kinetics, opening up new research and application prospects in materials science and catalytic chemistry.
[0004] Among these rare earth elements, the 5d orbital in the electronic structure of yttrium (Y) is empty, has strong redox ability, and can be used as an electron transfer station in catalytic reactions. In addition, the addition of a small amount of yttrium can improve the mechanical strength, electrical conductivity and thermal stability of the catalyst. Therefore, the use of inexpensive yttrium as a substitute for precious metals to prepare water splitting electrocatalysts has great research value. However, there is currently limited research on the introduction of Y elements as water electrolysis catalysts, and the effect of Y element incorporation on non-precious metal-based compounds and its mechanism of action are still unclear, and more extensive research is needed. Summary of the invention
[0005] The purpose of the present invention is to solve at least one of the technical problems existing in the prior art and to provide a YNiCoS x / NCF catalyst and preparation method thereof. Y and S were introduced into the NiCo foam matrix by a one-step hydrothermal method, and a YNiCo trimetallic sulfide with a multiphase structure was prepared in situ, so it was named YNiCoS x / NCF catalyst, where x is the number of S atoms. The catalyst exhibits excellent water splitting electrocatalytic activity under alkaline conditions. By introducing Y element, YNiCoS x The HER and OER performances of the catalysts were significantly enhanced. 10 and j 1000 The overpotential required for the current density is as low as 75mV and 332mV (HER), and 90mV and 399mV (OER), respectively. At high current density, it is even much better than the currently commercially available Pt / C and RuO2. At the same time, the catalyst exhibits good electrocatalytic stability in HER. 100 After running for 50 hours under the condition of x NCF||YNiCoS x NCF batteries only require 1.64V to generate 50mA / cm in an alkaline electrolyzer. 2 of current density.
[0006] The technical solution of the present invention is as follows:
[0007] On the one hand, the present invention provides a YNiCoS x The preparation method of the NCF catalyst comprises the following steps:
[0008] Clean and dry the NiCo foam;
[0009] Mix Y(NO3)2·6H2O, sulfur powder, N2H4 and deionized water to form a uniform mixture;
[0010] NiCo foam is placed in the mixed solution and reacted at a certain temperature to obtain YNiCoS x / NCF.
[0011] Preferably, the NiCo foam cleaning method comprises: ultrasonically cleaning the NiCo foam with acetone and hydrochloric acid respectively, and then washing it alternately with deionized water and anhydrous ethanol.
[0012] Preferably, the ultrasonic cleaning time is 10 to 20 minutes.
[0013] Preferably, the ratio of Y(NO3)2·6H2O, sulfur powder, N2H4 and deionized water is 0.06-0.18g: 0.03-0.07g: 1-4ml: 18-21ml.
[0014] Preferably, the ratio of Y(NO3)2·6H2O, sulfur powder, N2H4 and deionized water is 0.1-0.14 g: 0.04-0.06 g: 2-3 ml: 19-20 ml.
[0015] Preferably, the ratio of Y(NO3)2·6H2O, sulfur powder, N2H4 and deionized water is 0.12g:0.05g:2ml:20ml.
[0016] Preferably, the mixing process of Y(NO3)2·6H2O, sulfur powder, N2H4 and deionized water comprises: first stirring with a magnetic stirrer for 10 to 20 minutes, and then subjecting to 80 to 120W ultrasonic treatment for 10 to 20 minutes.
[0017] Preferably, the reaction temperature is 160-200° C., and the reaction time is 5-15 h.
[0018] Preferably, the reaction temperature is 180° C. and the reaction time is 10 h.
[0019] The second aspect of the present invention provides a YNiCoS prepared by the above method. x / NCF catalyst. x EDX element spectrum analysis of the / NCF catalyst shows that the S element is evenly dispersed on the catalyst surface. The weight percentages of S, Co, Ni, and Y in the catalyst are 33.46%, 49.44%, 16.47%, and 0.63%, respectively, which further verifies the existence of YNiCo sulfide.
[0020] YNiCoS of the present invention x / NCF catalysts exhibit excellent electrocatalytic activity, and the reasons can be summarized as follows: First, compared with single metal sulfides, NiCo alloys exhibit higher structural stability due to the synergistic effect between metals, and can effectively cope with the challenges under high current density; second, by introducing the rare earth element yttrium (Y), the NiCo sulfide catalyst was modified with the help of the unique redox ability of yttrium. After the introduction of yttrium, the crystal phase and morphology of NiCo sulfide changed, exposing more active sites, thereby increasing the electrochemical active surface area of the catalyst; third, the rich heterogeneous interfaces in the catalyst are more conducive to the adsorption of hydrogen intermediates and enhance the inherent activity of the active sites on the catalyst surface; fourth, the in situ growth of ternary metal sulfides on the NiCo foam substrate ensures good electrical conductivity and accelerates the electron transfer rate.
[0021] The present invention has at least one of the following beneficial effects:
[0022] The present invention adopts a one-step hydrothermal method to in situ prepare a multiphase structure YNiCo trimetallic sulfide with excellent electrical conductivity, structural stability and hydrolysis performance on a NiCo foam matrix. The catalyst exhibits excellent water splitting electrocatalytic activity under alkaline conditions. By introducing the Y element, YNiCoS x The HER and OER performances of the catalysts were significantly enhanced. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 YNiCoS of the present invention x / NCF catalyst preparation process flow chart.
[0024] Figure 2 The HER (a) and OER (b) performance comparisons of the catalysts prepared in Example 1 and Comparative Examples 1-2 are shown.
[0025] Figure 3 The HER (a) and OER (b) performance comparisons of the catalysts prepared in Examples 1 to 5 at different holding times, as well as the HER (c) and OER (d) performance comparisons at different temperatures.
[0026] Figure 4 HER (a) and OER (b) performance comparison of the catalysts prepared in Examples 1 and 6-7.
[0027] Figure 5 HER (a) and OER (b) performance comparison of the catalysts prepared in Examples 1 and 8-9.
[0028] Figure 6 HER (a) and OER (b) performance comparison of the catalysts prepared in Examples 1 and 10-11.
[0029] Figure 7 is the XRD pattern of the catalyst prepared in Example 1.
[0030] Figure 8 The morphology and structure of the catalyst prepared in Example 1. (a-c) SEM images at different magnifications, (d) TEM image, (e) HRTEM image, (f) TEM image, (g) SAED image, and (h) elemental energy spectrum.
[0031] Fig. 9 The morphology and structure of the catalyst prepared in Example 1. (a, b) SEM images at different magnifications, (c) XRD image.
[0032] Fig.10 The morphology and structure of the catalyst prepared in Comparative Example 3. (a, b) SEM images at different magnifications, (c) XRD image.
[0033] Fig.11 It is the XPS spectrum of the catalyst prepared in Example 1. (a) XPS full spectrum, (b) Co 2p, (c) Ni 2p, (d) Y 3d, (e) S 2p and (f) O 1s.
[0034] Fig.12 The HER performance test diagrams of the catalysts prepared in Example 1 and the comparative example in 1 M KOH are shown in Figures 1 and 2. (a) LSV curve, (b) comparison of overpotentials of the catalysts at different current densities, (c) Tafel curve, (d) electrochemical impedance spectroscopy, (e) MA curve and (f) TOF curve.
[0035] Fig.13 1 is the Cdl diagram of the catalysts prepared in Example 1 and Comparative Examples 3-4. (a) YNiCoS x / NCF, (b)NiCoS x / NCF, (c) YNiCo / NCF, (d) NCF.
[0036] Fig.14 The catalyst prepared in Example 1 was dissolved in 1 M KOH j 100 It curve under current density.
[0037] Fig.15 It is the XRD image of the catalyst It prepared in Example 1 after testing.
[0038] Fig.16 The OER performance test diagrams of the catalysts prepared in Example 1 and Comparative Examples 3-4 in 1 M KOH are shown in Figures 1 and 2. (a) LSV curve, (b) comparison of overpotentials of the catalysts at different current densities, (c) Tafel curve, (d) electrochemical impedance spectroscopy, (e) MA curve, and (f) TOF curve.
[0039] Fig.17 The sustainability and long-term stability test diagram of the catalyst prepared in Example 1 during the OER process. (a) YNiCoS x / NCF catalyst in 1 M KOH j 100 It curve under current density, (b) YNiCoS x / NCF|| YNiCoS x LSV curves of overall water electrolysis of Pt / C||RuO2 and Pt / NCF in 1 M KOH. DETAILED DESCRIPTION
[0041] The present invention is further described in detail below with specific examples, but the present invention is not limited to the following specific examples.
[0042] Nickel-cobalt foam (NCF) was from Suzhou Taili Co., Ltd. with a thickness of 1 mm.
[0043] Nickel foam (NF) was sourced from Suzhou Taili Co., Ltd. and had a thickness of 1 mm.
[0044] The cobalt foam was sourced from Suzhou Taili Co., Ltd. and had a thickness of 1 mm.
[0045] Yttrium nitrate Y(NO3)2·6H2O, AR 99.9%, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0046] Sulfur powder, AR 98.5%, was purchased from Aladdin Reagent (Shanghai) Co., Ltd.
[0047] Hydrazine hydrate, AR 80%, was purchased from Shanghai Lingfeng Chemical Reagent Co., Ltd.
[0048] Acetone, AR 99.5%, was purchased from Hangzhou Shuanglin Chemical Reagent Co., Ltd.
[0049] Hydrochloric acid, AR 36%, was purchased from Hangzhou Shuanglin Chemical Reagent Co., Ltd.
[0050] Example 1
[0051] First, the NiCo foam (NCF) was cut into 1 cm × 1 cm slices, and then ultrasonically cleaned with acetone and hydrochloric acid for 15 min, respectively, and then rinsed alternately with deionized water and anhydrous ethanol, and dried for use.
[0052] 0.12 g Y(NO3)2 6H2O, 0.05 g sulfur powder and 2 ml N2H4 were placed in a polytetrafluoroethylene reactor liner filled with 20 ml deionized water, stirred for 15 min using a magnetic stirrer, and then subjected to 100 W ultrasonic treatment for 15 min to form a uniform mixed solution.
[0053] The dried NCF was placed in the reactor liner and then packaged into a stainless steel high-pressure reactor, and then transferred to an oven at 180°C for 10 h. When the reactor was cooled, it was rinsed alternately with deionized water and anhydrous ethanol to obtain YNiCoS x / NCF.
[0054] Example 2
[0055] The difference from Example 1 is that: the mixture is then transferred to an oven at 180°C for insulation. 5h . The rest is the same as Example 1.
[0056] Example 3
[0057] The difference from Example 1 is that: the mixture is then transferred to an oven at 180°C for insulation. 15h. The rest is the same as Example 1.
[0058] Example 4
[0059] The difference from Example 1 is: then transfer to 160℃ The mixture was kept in an oven for 10 h. Other aspects were the same as those in Example 1.
[0060] Example 5
[0061] The difference from Example 1 is: then transfer to 200℃ The mixture was kept in an oven for 10 h. Other aspects were the same as those in Example 1.
[0062] Example 6
[0063] The difference from Example 1 is that 0.12g Y(NO3)2 6H2O, 0.05g sulfur powder, 4ml N2H4 is placed in 18ml The deionized water was placed in a polytetrafluoroethylene reactor liner. Other conditions were the same as those in Example 1.
[0064] Example 7
[0065] The difference from Example 1 is that 0.12g Y(NO3)2 6H2O, 0.05g sulfur powder, 1ml N2H4 is placed in 21ml The deionized water was placed in a polytetrafluoroethylene reactor liner. Other conditions were the same as those in Example 1.
[0066] Example 8
[0067] The difference from Example 1 is that 0.12g Y(NO3)2 6H2O, 0.03g Sulfur powder and 2 ml of N2H4 were placed in a polytetrafluoroethylene reactor containing 20 ml of deionized water. Other steps were the same as those in Example 1.
[0068] Example 9
[0069] The difference from Example 1 is that 0.12g Y(NO3)2 6H2O, 0.07g Sulfur powder and 2 ml of N2H4 were placed in a polytetrafluoroethylene reactor containing 20 ml of deionized water. Other steps were the same as those in Example 1.
[0070] Example 10
[0071] The difference from Example 1 is that: 0.06g Y(NO3)2 6H2O, 0.05g sulfur powder and 2ml N2H4 were placed in a polytetrafluoroethylene reactor containing 20ml deionized water. Other steps were the same as those in Example 1.
[0072] Embodiment 11
[0073] The difference from Example 1 is that: 0.18g Y(NO3)2 6H2O, 0.05g sulfur powder and 2ml N2H4 were placed in a polytetrafluoroethylene reactor containing 20ml deionized water. Other steps were the same as those in Example 1.
[0074] Comparative Example 1
[0075] The difference from Example 1 is that "NiCo foam" is replaced by "Ni foam". The rest is the same as Example 1.
[0076] Comparative Example 2
[0077] The difference from Example 1 is that "NiCo foam" is replaced by "Co foam". The rest is the same as Example 1.
[0078] Comparative Example 3
[0079] The difference from Example 1 is that sulfur powder is not added to prepare YNiCo / NCF. Other aspects are the same as Example 1.
[0080] Comparative Example 4
[0081] The difference from Example 1 is that no Y(NO3)2 6H2O is added to prepare NiCoS x / NCF. Others are the same as in Example 1.
[0082] Testing and result analysis
[0083] The catalysts prepared in Examples 1 to 10 and Comparative Examples 1 to 4 were subjected to the following tests.
[0084] 1. Test method description
[0085] 1. Morphology and phase characterization
[0086] The appearance morphology of the synthesized catalyst was analyzed by field emission scanning electron microscopy (SEM), and the distribution of surface elements was observed by elemental energy spectrum. Transmission electron microscopy (TEM) was used to deeply detect and study the microstructure and interplanar spacing of the catalyst. X-ray diffractometer (XRD) characterized the crystal structure to evaluate the phase composition and degree of crystallinity of the sample. The composition and content of the elements in the material were determined by X-ray photoelectron spectroscopy (XPS), thereby determining the chemical composition of the catalyst and the evolution of the compound state.
[0087] 2. Electrochemical performance test
[0088] The electrochemical performance test was carried out at room temperature and atmospheric pressure using a typical three-electrode device using Shanghai Chenhua's CHI 660E / 750E electrochemical workstation. The system includes a catalyst working electrode, a mercury oxide electrode reference electrode and a carbon rod counter electrode, and the electrolyte is 1M KOH (pH = 14). The electrochemical tests cover cyclic voltammetry (CV), linear sweep voltammetry (LSV), electrochemical impedance spectroscopy (EIS), chronoamperometry (It), etc. First, the prepared electrode was pretreated using CV and activated 500 times at a scan rate of 50mV / s to ensure the stability and accuracy of the results. Then, the electrode was activated at a scan rate of 1mV s -1 The LSV test was performed in the voltage range of -2.4 to 0 V and 0 to 1.2 V at a scan rate to obtain the HER and OER performance. All polarization curves were IR compensated according to the ohmic resistance, and the corrected potential (E c ) According to formula E c =E m -IRs calculation, where E m For experimental measurement of potential, Rs is the solution resistance derived from the curve, and I is the current. The measured potential is calibrated as the overpotential under the reversible hydrogen electrode (RHE), and the calculation formula is E vs RHE = E vs Hg / HgO + 0.098 + 0.059 × pH. At the same time, using EIS technology at 10 5 The electrochemical impedance spectroscopy (EIS) diagrams reflecting the HER kinetics were plotted in the frequency range of 0.01 Hz to 0.01 Hz and the AC voltage amplitude of 5 mV. The long-term stability and durability of the catalyst were analyzed by measuring the electrochemical impedance spectroscopy (EIS) curves at 10 mV s -1 Continuous 10 4 The catalytic materials were assembled into a dual-electrode system with anode and cathode to explore the overall water splitting performance of the catalyst.
[0089] 2. Test Results and Analysis
[0090] 1. YNiCoS x Parameter optimization of NCF catalyst
[0091] In order to explore the optimal catalyst synthesis method, the present invention studies the morphology and HER and OER activities of metal sulfides synthesized under different conditions.
[0092] (1) Foam Type
[0093] like Figure 2As shown, the electrochemical properties of metal sulfides prepared from different metal foam substrates vary greatly. The metal sulfide prepared using pure nickel foam (Comparative Example 1) has the worst performance in the OER reaction. This result may be attributed to the poor structural stability of a single metal, and the catalyst falls off under high current density testing. The metal sulfide prepared using pure cobalt foam (Comparative Example 2) is better than pure nickel foam (Comparative Example 1), and the use of nickel-cobalt alloy foam (Example 1) as a self-supporting skeleton can maintain stable hydrogen and oxygen evolution at high current density due to the better stability of the alloy structure.
[0094] (2) Temperature and time of hydrothermal reaction
[0095] The present invention also explores the effect of the temperature and time of the hydrothermal reaction on the YNiCoS x / NCF catalyst catalytic activity.
[0096] Figure 3 (a, b) show the HER and OER performances in the hydrothermal reaction after keeping warm for 5h, 10h, and 15h. The results show that the reaction activity is best at 10h.
[0097] Figure 3 (c, d) show the electrocatalytic performance under reaction conditions of 160°C, 180°C, and 200°C. It is found that the HER and OER activities are optimal at 180°C. This may be because at suitable temperature and growth time, the structure and morphology of the catalyst lead to more active sites, which is conducive to hydrogen evolution and oxygen evolution reactions.
[0098] (3) Hydrazine hydrate concentration
[0099] The concentration of hydrazine hydrate provides different environments for the growth of catalysts. Figure 4 As shown in the figure, the volume ratio of N2H4 to deionized water of 2:20 is significantly better than that of N2H4 to deionized water of 1:21 and 4:18, indicating that both too high and too low concentrations of hydrazine hydrate lead to a decrease in the performance of the prepared catalyst. This may be because the appropriate concentration ratio can make the reaction proceed more fully.
[0100] (4) Amount of sulfur powder and Y(NO3)2 6H2O
[0101] By comparing the overpotential of the catalyst under the same current density, the results are as follows Figures 5-6 shown.
[0102] Depend on Figures 5-6It can be seen that 0.05g sulfur powder and 0.12g Y(NO3)2 6H2O are better than 0.03g sulfur powder and 0.06g Y(NO3)2 6H2O, 0.07g sulfur powder and 0.18g Y(NO3)2 6H2O), and the corresponding optimal parameters are 0.05g sulfur powder and 0.12g Y(NO3)2 6H2O. The reason may be that the appropriate solvent concentration plays an important role in the growth and distribution of the catalyst.
[0103] 2. YNiCoS x Morphology and structure analysis of NCF catalyst
[0104] To further explore the YNiCoS x The relationship between the structure of the YNiCoS / NCF catalyst and its electrocatalytic performance was investigated by XRD. x The crystal structure of the / NCF catalyst was characterized.
[0105] like Figure 7 As shown, the diffraction peaks at 32.7°, 55.7°, 75.7°, and 87.2° are attributed to the (200), (311), (331), and (422) crystal planes of YS (JCPDS NO.18-1478). The diffraction peaks at 29.8°, 31.1°, 39.4°, 47.5°, 51.9°, 61.7°, 72.9°, 76.8°, and 84.5° are attributed to the (311), (222)(331), (511), (440), (622), (731), (800), and (751) crystal planes of Co4S3 (JCPDS NO.02-1338). The diffraction peaks at 29.6° and 49.3° are attributed to the (111) and (220) crystal planes of Ni3S2 (JCPDS NO.27-0341). These results indicate that the sulfide of YNiCo was successfully synthesized by a one-step hydrothermal method. In addition, the diffraction peaks at 29.7°, 41.3°, 43.8°, and 84.1° belong to the (201), (202), (020), and (521) crystal planes of NiY (JCPDS NO.65-5276), which is consistent with the NiY alloy synthesized in the comparative sample YNiCo.
[0106] In addition, for YNiCoS x The morphology of the NCF / C catalyst was characterized. Figure 8 (a~c) are YNiCoS x From the SEM images of the NiCo / NCF catalyst at different magnifications, it can be observed that a sphere composed of many irregular nanoparticles is in situ grown on the NiCo foam skeleton, with some rectangular nanosheets interspersed at the edge of the sphere. In order to further explore its structure, a transmission electron microscope was used to characterize it. Figure 8(d) shows a TEM image at low magnification, showing rectangular nanosheets and irregular particles. The two morphologies were analyzed using transmission electron microscopy at high magnification, where Figure 8 (e) is a rectangular sheet. In the figure, we can find the (200) crystal plane of YS, the (220) crystal plane of Ni3S2, the (222) crystal plane of Co4S3 and the (211) crystal plane of NiY, which is consistent with the results of XRD. Figure 8 (f) is a high-magnification TEM image of irregular particles, in which the (311) and (211) crystal planes of Co4S3 and the (111) crystal plane of Ni3S2 can be found. Figure 8 In (e, f), staggered stripes can be observed at the junctions between crystal planes, indicating that abundant heterogeneous interfaces are formed in the catalyst. The formed heterogeneous interfaces and stacking faults can usually adapt to the stress in the crystalline material, which plays an important role in regulating the catalytic active sites. Figure 8 (g) is the selected area electron diffraction (SAED) pattern of the corresponding area, from which the (400) crystal plane of Co4S3, the (111) crystal plane of Ni3S2, and the (303) and (020) crystal planes of NiY can be observed. These results show that the YNiCo trimetallic sulfide was successfully synthesized by a one-step method, and the sulfide has a complex heterogeneous structure, which is of great significance for improving the catalytic activity of HER and OER. In order to explore the YNiCoS x To investigate the element distribution of the NCF / C catalyst, we performed EDX element spectrum analysis on the surface of the catalyst. The results are shown in Figure 8 As shown in (h), it can be seen that the S element is evenly dispersed on the catalyst surface. The weight percentages of S, Co, Ni, and Y in the catalyst are 33.46%, 49.44%, 16.47%, and 0.63%, respectively. This result further verifies the existence of YNiCo sulfide.
[0107] In order to explore the effect of the addition of Y element on the morphology and structure of the catalyst, the NiCoS prepared in Example 1 was x The morphology and crystal structure of the / NCF catalyst were characterized.
[0108] Fig. 9 (a) shows NiCoS x From the SEM image of the NiCo / NCF catalyst, it can be observed that a spherical structure composed of irregular particles also grew on the NiCo foam skeleton, which is similar to the Figure 8 (a, b) shows YNiCoS xUnlike the NCF / YC catalyst, there are no rectangular nanosheets formed at the edges of these spherical structures, but some irregular particles instead. By comparing the morphological structures of the two catalysts, it can be inferred that the addition of Y element provides new crystal nuclei for the growth of the catalyst, resulting in different morphologies.
[0109] By analyzing NiCoS x The XRD pattern of / NCF further explored the effect of Y element on the catalyst structure. Fig. 9 (c) shows that the YNiCoS x Compared with NiCoS / NCF catalyst, x / NCF has different Co sulfide crystal phases, among which the diffraction peaks at 35.3°, 46.7°, 51.9°, and 74.3° correspond to the (101), (102), (003), and (202) crystal planes of Co4S3 (JCPDS NO.02-1458), respectively. The diffraction peaks at 29.9°, 30.8°, 43.5°, 64.3°, and 72.5° correspond to the (100), (002), (102), (004), and (104) crystal planes of CoS (JCPDS NO.65-0407), respectively. The crystal phase of Ni3S2 is similar to that of YNiCo x / NCF catalyst, it can be inferred that the addition of Y element changes the crystal phase of Co sulfide, but does not change the crystal phase of Ni sulfide.
[0110] As a comparison, the present invention also explored the morphology and structure of the catalyst synthesized in Comparative Example 3 (without adding sulfur powder as a reactant). Fig.10 (a, b) show the SEM images of YNiCo / NCF. Some irregularly shaped particles grow on the NiCo foam skeleton. Under a high-magnification microscope, groove-like substances are observed on the surface of the foam skeleton. The crystal structure of the YNiCo / NCF catalyst was then characterized. Fig.10 It can be seen from the XRD image of (c) that the diffraction peaks correspond to the NiY (JCPDS NO.65-5276) and Co5Y (JCPDS NO.17-0078) crystal phases. It can be reasonably inferred that when sulfur powder is not used as a reactant, the catalyst synthesized under the same other parameters is an alloy of Ni, Co and Y.
[0111] X-ray photoelectron spectroscopy (XPS) was used to characterize the YNiCoS prepared in Example 1. x The chemical state and composition of the NCF catalyst were characterized. Fig.11 As shown. Fig.11 (a) illustrates the presence of Ni, Co, S, Y and O elements in the sample. Fig.11(b) is the high-resolution XPS spectrum of Co 2p. The core energy level spectrum in the figure can be deconvoluted into two oscillating satellite peaks (about 786.5eV and 802.3eV) and four main peaks. Among them, there are two unique spin-orbit peaks at 778.3 and 793.4eV, corresponding to Co 0 Co 2p 3 / 2 and Co 2p 1 / 2 Meanwhile, the other two peaks at 781.0 eV and 796.8 eV are attributed to Co 2+ Co 2p 3 / 2 and Co 2p 1 / 2 .
[0112] Fig.11 (c) shows the XPS high-resolution spectrum of Ni, where 853.1 eV and 870.2 eV are attributed to Ni 2+ Ni 2p 3 / 2 and Ni 2p 1 / 2 , the peaks at 855.8eV and 873.6eV are attributed to Ni 3+ Ni 2p 3 / 2 and Ni 2p 1 / 2 In addition, the peaks at 861.5 and 879.6 are two oscillation satellite peaks of Ni. Fig.11 (d) is the signal peak of Y 3d. The fitting peaks at 156.7 eV and 158.1 eV are consistent with those of Y 3d. 5 / 2 and Y3d 3 / 2 The chemical state of S is consistent with that of YNiCo, indicating that Y and the element are successfully loaded into the YNiCo sulfide catalyst. Fig.11 As shown in (e), the peaks at 161.6 eV and 162.8 eV are attributed to S 2- S2p 3 / 2 and S2p 1 / 3 , the peaks at 162.2eV and 163.1eV are attributed to S2 2- S2p 3 / 2 and S2p 1 / 3 In addition, the metal sulfide was successfully synthesized by a one-step hydrothermal method, which is consistent with the results shown by XRD. The peaks at 168.2eV and 169.3eV are attributed to SO4 2- SO bond in the sulfide. The possible reason is that the sulfide exposed to air is oxidized to form SO4 2- . Fig.11(f) shows the XPS peak spectrum of O1s, where the peak at 531.5 eV is attributed to the CO bond, and the peak at 532.7 is attributed to the COH bond. Through XPS quantitative analysis of each element, the atomic percentages of Co 2p, Ni 2p, Y 3d, and S2p are 9.94%, 6.14%, 3.73%, and 15.84%, respectively, which indirectly confirms that the Y element has been successfully added to YNiCoS x / NCF catalyst.
[0113] 3. YNiCoS x Electrochemical performance of NCF catalysts
[0114] The HER performance of the catalyst prepared in Example 1 was studied in 1 M KOH electrolyte using a standard three-electrode configuration. Fig.12 (a) shows the YNiCoS after IR correction x / NCF,NiCoS x Linear sweep voltammetry (LSV) polarization curves of / NCF, YNiCo / NCF, NCF and Pt / C catalysts.
[0115] Fig.12 (b) The different catalysts are 10 、j 100 and j 1000 Overpotential comparison diagram under current density. Note that YNiCoS x / NCF exhibits excellent electrocatalytic performance, driving j 10 and j 100 The overpotential of NiCoS is only 75mV and 209mV, which is significantly lower than that of NiCoS x / NCF(109mV / j 10 , 282mV / j 100 ), YNiCo / NCF(182mV / j 10 , 323mV / j 100 ), NCF(163mV / j 10 , 317mV / j 100 ). More importantly, YNiCoS x / NCF Maintain 500 and j 1000 The high current density of Pt / C only requires an overpotential of 291 mV and 332 mV, respectively, which is better than Pt / C (356 mV / j 500 , 498mV / j 1000 ), meeting the potential application needs of H2 production under industrial conditions. Tafel value is of great significance in analyzing electrochemical reaction kinetics.
[0116] Fig.12(c) shows the Fig.12 (a) The Tafel slopes of different catalysts derived from the experiment show that YNiCoS prepared in Example 1 x The Tafel slope of NCF is 112.5mV dec -1 , which is much smaller than the NiCoS prepared in Comparative Example 4 x / NCF(163.7mV dec -1 ), YNiCo / NCF prepared in Comparative Example 3 (189.9mV dec -1 ) and NCF (192.3mV dec -1 ), indicating that the catalyst has a faster reaction kinetics. The Tafel slope values corresponding to the three-step elementary reactions of HER in alkaline electrolyte are: the Tafel value of the Volmer reaction is greater than 120mV dec -1 The Tafel value of the Heyrovsky reaction ranges from 40 to 120 mV dec. -1 The Tafel value of the Tafel reaction is less than 30mV dec -1 , according to YNiCoS x / NCF(112.5mV dec -1 ) has a Tafel slope of 40 to 120 mV dec -1 It can be concluded that the HER reaction kinetics in alkaline medium follows the Volmer-Heyrovsky mechanism.
[0117] In addition, we investigated the electrocatalytic kinetics of different catalysts by electrochemical impedance spectroscopy (EIS). Fig.12 The electrochemical impedance spectroscopy in (d) shows that YNiCoS x The interfacial charge transfer resistance (R ct ) is only 7.3Ω, much smaller than NiCoS x / NCF (11.9Ω), YNiCo / NCF (48.3Ω) and NCF (61.4Ω), which makes YNiCoS x / NCF catalysts have higher electrical conductivity and can achieve rapid electron transfer at a higher rate, achieving higher catalytic activity. Mass activity (MA) and turnover frequency (TOF) are two other important parameters used to evaluate catalytic activity, such as Fig.12 (e) shows that YNiCoS x The mass activity of NCF at the same voltage is significantly higher than that of NiCoS x / NCF and YNiCo / NCF. Specifically, at an overpotential of 300 mV, YNiCoS x The mass activity of NCF is 92.2Ag-1 , while NiCoS x / NCF and YNiCo / NCF have only 16.7Ag -1 and 8.75Ag -1 , which indicates that in the catalyst of the same mass, YNiCoS x / NCF catalysts achieve higher hydrogen evolution efficiency. In order to better explore the intrinsic activity of the catalysts, the turnover frequencies of the catalysts were compared, such as Fig.12 As shown in (f), compared with NiCoS x / NCF and YNiCo / NCF, YNiCoS x / NCF has a larger turnover frequency at the same overpotential, which may be due to the fact that NiCoS x / NCF has abundant heterogeneous interfaces, which is more conducive to the adsorption of hydrogen intermediates and enhances the intrinsic activity of active sites exposed on the catalyst surface.
[0118] In order to further explore the reasons for the improvement of HER activity, the present invention measured the electrochemical surface area (ECSA) of the catalysts prepared in Example 1 and Comparative Examples 3 to 4 by double layer capacitance method (Cdl). Fig.13 As shown in Figure 2, the scan rate in the non-Faraday range is from 20 to 200 mV s -1 CV curve (left) and its calculated Cdl value (right). x The Cdl value of / NCF is 51.4mF cm -2 , than NiCoS x / NCF(36.4mF cm -2 )、YNiCo / NCF(4.3mF cm -2 ) and NCF (4.9mF cm -2 ) are 1.3, 10.9 and 9.4 times larger, respectively. It is worth noting that the introduction of Y element changes the original morphology of NiCo sulfide, and the rectangular nanosheets formed increase the specific surface area of the catalyst. By comparing the electrochemical surface areas between the catalysts, it is further confirmed that YNiCoS x The multiphase structure of / NCF exposes more active sites and has higher catalytic efficiency.
[0119] In addition to catalytic activity, the stability of electrocatalytic hydrogen evolution is also an important indicator for evaluating electrode materials. The chronoamperometry (It) method was used to investigate the electrocatalytic stability of the YNiCoS prepared in Example 1. x / Long-term stability and durability of NCF catalysts. Fig.14 Demonstrated YNiCoS xThe change process of the YNiCoS / NCF catalyst maintaining a current density of 100 mA within 50 h at a fixed voltage. According to the experimental results, after 50 h of continuous hydrogen evolution reaction, the current density only decreased by 4%, which indicates that the YNiCoS prepared by the one-step method x / NCF catalyst has excellent stability in HER.
[0120] In addition, the crystal phase of the samples after stability test was characterized. Fig.15 It can be seen that after the It test at 100mA current density for 50h, the YNiCoS x The XRD diffraction peaks of the / NCF catalyst are attributed to YS (JCPDS NO.18-1478), Co4S3 (JCPDS NO.02-1338), Ni3S2 (JCPDS NO.27-0341), and NiY (JCPDS NO.65-5276), which are consistent with the crystal structure of the catalyst before the It test, indicating that the properties of the catalyst did not change before and after the reaction, which indirectly confirms that the YNiCoS x / NCF catalyst has excellent stability in alkaline hydrogen evolution reaction and can adapt to the environment of long-term continuous hydrogen evolution.
[0121] In addition, the present invention also explores the OER performance of the catalysts prepared in Example 1 and Comparative Examples 3 to 4 in 1 M KOH electrolyte. Fig.16 (a) YNiCoS after IR correction x / NCF、NiCoS x Linear sweep voltammetry (LSV) polarization curves of / NCF, YNiCo / NCF, NCF and Pt / C catalysts. Fig.16 (b) The different catalysts are 10 、j 100 and j 800 Overpotential comparison diagram under current density. Among them, YNiCoS x / NCF exhibits excellent electrocatalytic performance, driving j 10 and j 100 The overpotential of NiCoS is only 90mV and 290mV, which is significantly lower than that of NiCoS x / NCF(122mV / j 10 , 329mV / j 100 )、YNiCo / NCF(314mV / j 10 , 323mV / j 100 ) and NCF(320mV / j 10 , 388mV / j 100 ). In addition, YNiCoS x / NCF Maintain500 and j 800 The high current density of the two electrodes only requires an overpotential of 368 mV and 399 mV, respectively, which is better than that of RuO2 (429 mV / j 500 , 482mV / j 800 ). At high current density, YNiCoS x / NCF shows better performance than RuO2, which may be due to the in-situ growth of the catalyst on the foam skeleton, which has better structural stability and can stably evolve oxygen at high current density, which also indirectly confirms the feasibility of the in-situ engineering strategy. The Tafel value reflects the information of OER kinetics. Fig.16 (c) shows the Fig.16 (a) The calculated Tafel slopes of different catalysts. The smaller the Tafel slope, the faster the reaction kinetics. x The Tafel slope of NCF is 114.7mV dec -1 , which is smaller than NiCoS x / NCF(136.4mV dec -1 )、YNiCo / NCF(119.1mV dec -1 )、NCF(169.2mV dec -1 ) and RuO2 (160.7mV dec -1 ), indicating YNiCoS x / NCF catalyst has faster reaction kinetics.
[0122] Electrochemical impedance spectroscopy (EIS) allows us to investigate the reaction kinetics of different catalysts. Fig.16 As shown in the electrochemical impedance spectroscopy in (d), YNiCoS x The interfacial charge transfer resistance (Rct) of / NCF is only 0.98Ω, which is much smaller than that of NiCoS x / NCF (1.58Ω), YNiCo / NCF (19.09Ω), NCF (38.59Ω) and RuO2 (2.13Ω), which makes YNiCoS x / NCF catalyst has faster electron transfer rate and achieves better catalytic activity.
[0123] Here, we also use mass activity (MA) and turnover frequency (TOF) to evaluate the intrinsic catalytic activity of the catalyst, such as Fig.16 (e) shows that YNiCoS x The mass activity of NCF at the same voltage is significantly higher than that of NiCoS x / NCF and YNiCo / NCF. Specifically, at an overpotential of 300 mV, YNiCoSx The mass activity of NCF is 19.6Ag -1 , while NiCoS x / NCF and YNiCo / NCF are only 8.0Ag -1 and 0.8Ag -1 In order to better explore the intrinsic activity of the catalyst, we compared the turnover frequencies of the catalysts, such as Fig.16 As shown in (f), compared with NiCoS x / NCF and YNiCo / NCF, YNiCoS x / NCF has a greater turnover frequency at the same overpotential. From the MA and TOF data, it can be seen that the intrinsic catalytic activity of NiCo sulfide is much higher than that of NiCoY alloy, indicating that sulfide is more favorable than metal alloys in the OER process. At the same time, by introducing the Y element, the original NiCo sulfide crystal structure is changed, and the YNiCo multiphase metal sulfide grown in situ on the catalyst surface provides a rich heterogeneous interface structure, which is conducive to regulating the catalytic active sites and showing considerable catalytic activity in the OER process, even much higher than RuO2 at high current density. This also confirms from another aspect that the performance and stability of the alloy can be improved by introducing foreign elements.
[0124] Furthermore, the sustainability and long-term stability of the prepared catalysts in the OER process were explored under testing conditions similar to HER. Fig.17 (a) YNiCoS x It curve of the / NCF catalyst in 1M KOH at a current density of 100 mA. It can be seen that after 5 h of oxygen evolution reaction, the current density decreased, indicating that although the synthesized catalyst has considerable performance in the LSV test of OER, the stability of the catalyst needs to be improved in a continuous oxygen evolution environment.
[0125] On the other hand, YNiCoS x / NCF catalysts as cathode and anode electrodes can enhance the overall water splitting performance of its two-electrode system. Fig.17 (b) shows the current density j used to deliver the constructed battery. 50 The cell voltage obtained was about 1.64 V, which is similar to the cell voltage (1.63 V) loaded with noble metal Pt / C and RuO2 catalysts. This observation shows that through rational design, non-noble metal-based bifunctional catalysts with performance comparable to commercial noble metal catalysts can be prepared, providing hope for replacing noble metal catalysts.
[0126] Based on the above analysis, the present invention successfully synthesized YNiCo ternary multiphase sulfide with excellent electrical conductivity, structural stability and hydrolysis performance through a one-step hydrothermal method. At high current density, its performance even surpasses that of some precious metal-based catalysts. The present invention not only explores the influence of the rare earth element yttrium on the structure of non-precious metal-based sulfides and the performance of hydrogen and oxygen evolution in water electrolysis, but also provides a valuable reference for further research on the yttrium element in the field of water electrolysis.
[0127] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A YNiCoS x / A method for preparing a NCF catalyst, characterized in that: The following steps are involved: Clean and dry the NiCo foam; Mix Y(NO3)2·6H2O, sulfur powder, N2H4 and deionized water to form a uniform mixture; NiCo foam is placed in the mixed solution and reacted at a certain temperature to obtain YNiCoS x / NCF.
2. A YNiCoS according to claim 1 x / A method for preparing a NCF catalyst, characterized in that: The NiCo foam cleaning method comprises: ultrasonically cleaning the NiCo foam with acetone and hydrochloric acid respectively, and then washing it alternately with deionized water and anhydrous ethanol.
3. A YNiCoS according to claim 1 x / A method for preparing a NCF catalyst, characterized in that: The ultrasonic cleaning time is 10 to 20 minutes.
4. A YNiCoS according to claim 1 x / A method for preparing a NCF catalyst, characterized in that: The ratio of Y(NO3)2·6H2O, sulfur powder, N2H4 and deionized water is 0.06-0.18g: 0.03-0.07g: 1-4ml: 18-21ml.
5. A YNiCoS according to claim 1 x / A method for preparing a NCF catalyst, characterized in that: The ratio of Y(NO3)2·6H2O, sulfur powder, N2H4 and deionized water is 0.1-0.14g: 0.04-0.06g: 2-3ml: 19-20ml.
6. A YNiCoS according to claim 1 x / A method for preparing a NCF catalyst, characterized in that: The ratio of Y(NO3)2·6H2O, sulfur powder, N2H4 and deionized water is 0.12g:0.05g, 2ml:20ml.
7. A YNiCoS according to claim 1 x / A method for preparing a NCF catalyst, characterized in that: The mixing process of Y(NO3)2·6H2O, sulfur powder, N2H4 and deionized water comprises: firstly stirring with a magnetic stirrer for 10 to 20 minutes, and then subjecting to 80 to 120W ultrasonic treatment for 10 to 20 minutes.
8. A YNiCoS according to claim 1 x / A method for preparing a NCF catalyst, characterized in that: The reaction temperature is 160-200° C., and the reaction time is 5-15 hours.
9. A YNiCoS according to claim 1 x / A method for preparing a NCF catalyst, characterized in that: The reaction temperature is 180° C. and the reaction time is 10 h.
10. YNiCoS prepared by the method according to any one of claims 1 to 9 x / NCF catalyst.
Citation Information
Cited By
Self-supporting nickel iron selenide electrolyzed water catalyst as well as preparation method and application thereof
CN120291123A